IMPROVING GROSS MOTOR SKILLS THROUGH TRADITIONAL RUBBEE ROPE JUMPING GAMES FOR CHILDREN AGED 5-6 YEARS - Suirah, Ayu Fajarwati, Iman Sampurna (Jurnal Pendidikan dan Penelitian Semesta Mendidik, 2024)
Physical motor development is an important factor in the overall development of an individual, therefore teachers are able to improve children's gross motor skills by doing various activities that can stimulate and develop gross motor skills. This study aims to reveal the role of traditional games to improve children's gross motor skills. The subjects of this study were 14 students aged 5-6 years consisting of 7 boys and 7 girls. The methodology in this study used classroom action research which included four stages, namely: planning, action, observation, and reflection carried out in two cycles. The results of this study concluded that the gross motor skills of early childhood can be developed through traditional rubber jump rope games by fulfilling several indicators, namely children are able to maintain body balance, can maintain body strength while playing, and can play agilely.